Copyright Regulation of AI-Generated Works : A Comparative Study of Indonesia, the United States, and Germany - Agustianto; Sherney Z.; Hari Sutra Disemadi (Vifada Assumption Journal of Law, 2026)
Purpose: This study examines copyright regulation in the era of AI through a comparative legal analysis between Indonesia, the United States, and Germany, with the primary aim of analyzing how the copyright regulatory frameworks in the three countries accommodate AI-generated works and to identify regulatory gaps that may hinder legal certainty in the context of generative AI. Research Design and Methodology: This study uses normative legal research methods with statutory and comparative legal approaches, analyzing legal implications of AI-generated works and conducting an assessment of the relevant primary law sources.  Findings and Discussion: Findings highlight that Germany stands out as the most advanced through the amendment of UrhG and the adoption of the DSM Directive, while the United States follows with clear output regulation through USCO policies. Indonesia lags behind, still relying on Law No. 28 of 2014’s rather classical understanding of copyrights. The research identifies two major gaps that create legal challenges: regulatory preparedness and legal uncertainty around output and input layers. Implications: This study recommends a two-layer reform direction for Indonesian copyright law by proposing clearer rules on AI-generated outputs and the use of copyrighted works as AI training inputs, drawing from the United States’ human authorship and Germany’s text and data mining framework. The contribution of this study lies in its addition to the growing body of literature around generative AI in the legal sphere and practical implications for future legal development.